Pendidikan Karakter dalam Kitab Ayyuhal Walad Karya Imam Al-Ghazali - Maghfirotun, Khubni; Aprilio, Yuda (Fakultas Agama Islam Universitas Billfath, 2022)
This Study aims to describe and analyze the values ​​of character education in Imam al-Ghazali's Ayyuhal Walad book, as well as to describe and analyze the relevance of character education in Imam al-Ghazali's Ayyuhal Walad book to education today. The values ​​of character education in the Ayyuhal Walad book are education that prints the character, personality, character, behavior, or morals of a child according to the Ayyuhal Walad book according to Imam al-Ghazali's view. In this case, the researcher will relate the value of character education in the book of Ayyuhal Walad with character education in this millennial era. Based on the research conducted, it was found that: (1)The values ​​of character education in the book of Ayyuhal Walad are religious values, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the homeland, appreciate achievements, friendly/communicative, peace-loving, fond of reading, social care, and responsibility. (2) The relevance of character education values ​​in the book of Ayyuhal Walad with character education in this millennial era is very relevant.